Retroperitoneal tumor invasion of the inferior vena cava.A single-centre experience in tumor thrombectomy - Georgopoulos, S.; Felekouras, E.; Markatis et al., F. (Acta Biomedica Atenei Parmensis, 2011)
Background and aim: Radical surgical treatment improves survival in patients suffering from retroperitoneal tumors with co- existing inferior vena cava thrombus. The extraction excision can be performed through many techniques such as liver mobilization which is performed in liver transplantation procedures. Methods: During 2000-2007, 11 patients with retroperitoneal tumors and inferior vena cava thrombus were surgically treated in our department. Classification of the thrombus was defined as suggested by Neves and Zinke. All patients were categorized as level I or level II. In all cases a transabdominal approach, liver mobilization and extraction of the thrombus by milking down or Fogarty catheter were used. Results: No peri-operative mortality was observed. One case of pulmonary embolisation was conservatively treated. One patient presented recurrence 6 months after the procedure. Conclusions: The use of liver transplantation techniques in the surgical management of retroperitoneal tumors with inferior vena cava thrombus, is a safe procedure that improves the survival of these patients.